In Situ Prepared Microemulsion-polymer Flooding in Enhanced Oil Recovery—A Review - Jeirani, Z.; Mohamed Jan, B.; Si Ali, B.; See, C.H.; Saphanuchart, W. (Taylor & Francis, 2014)
Microemulsion could be formed in situ through simultaneous injection of surfactant, cosurfactant, and brine into the reservoir. The formed microemulsion is expected to propagate toward the production well and along its way sweep significant amounts of the remaining hydrocarbon in the reservoir. There are numerous reports on in situ prepared microemulsion flooding in the literature. The interest in in situ prepared microemulsion flooding research activities is expected to increase tremendously in the near future because of its high potential in maximizing hydrocarbon recovery in enhanced oil recovery activities. The authors summarize major articles relevant to in situ prepared microemulsion flooding with application of various polymers in the flooding. They also discuss critically and extensively the effect and function of polymers and their role in the microemulsion flooding. This review opens new horizons for future research on in situ prepared microemulsion-polymer flooding in enhanced oil recovery processes by systematically organizing and comparing data in the literature. The data and information presented would be very useful to researchers conducting work related to enhanced oil recovery with microemulsion polymer flooding.